Negative electrode composite, method for preparing the same, negative electrode sheet, and battery
Patent Information
- Application Number
- CN202510934056.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-07
AI Technical Summary
[0005]有鉴于此,本发明致力于提供一种负极复合材料及其制备方法、负极极片和电池,以解决现有技术中锑钼过渡金属硫化物负极材料导电性和循环稳定性差的问题
[0023](1)本发明的MoS2@Sb2S3@rGO纳米材料整体呈纳米棒状结构,棒状结构具有较为规则的形状和方向性,能够减缓和分散体积膨胀所带来的应力。棒状形貌可以使得在充放电过程中,材料的体积变化在一定方向上更加的均匀,减少了材料内部应力集中,提高结构稳定性和循环寿命。棒状结构能够更好地连接各个颗粒,降低电子传输的障碍,改善电池整体导电性能。棒状结构具有较高的机械强度,相比于颗粒状或其他形貌的材料,棒状结构能够更好地承受反复的体积变化,避免材料的断裂和粉化。棒状结构具有良好的分散性,避免了颗粒堆积和团聚的问题。
Smart Images

Figure CN121054647B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy storage technology, specifically to a negative electrode composite material and its preparation method, a negative electrode sheet, and a battery. Background Technology
[0002] Lithium-ion batteries, as high-energy-density and long-life energy storage devices, have been widely used in consumer electronics, energy storage systems, and electric vehicles. The anode material, as a crucial component of lithium-ion batteries, directly affects the battery's cycle life, charge / discharge efficiency, and safety. While traditional graphite anode materials possess high initial capacity, they are prone to structural collapse during high-rate charge / discharge processes, leading to capacity reduction.
[0003] In recent years, transition metal sulfides (such as MoS2) and antimony sulfides (such as Sb2S3) have become potential anode materials for lithium-ion batteries due to their high theoretical capacity and good electrochemical stability. However, these materials face problems such as poor conductivity, large volume expansion, and fragility in practical applications, which greatly limits their development in lithium-ion batteries.
[0004] Therefore, how to provide a simple and efficient method for preparing antimony-molybdenum transition metal sulfide anode materials, while improving the capacity and energy of lithium-ion batteries, and simultaneously enhancing their conductivity and cycle stability, is a pressing technical challenge that needs to be addressed. Summary of the Invention
[0005] In view of this, the present invention aims to provide a negative electrode composite material and its preparation method, a negative electrode sheet and battery, so as to solve the problems of poor conductivity and cycle stability of antimony-molybdenum transition metal sulfide negative electrode materials in the prior art.
[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows:
[0007] A first aspect of the present invention provides a negative electrode composite material, the negative electrode composite material comprising MoS2@Sb2S3@rGO nanomaterials; the MoS2@Sb2S3@rGO nanomaterials being a rod-shaped structure formed by stacking several nanosheets;
[0008] The nanosheet includes a first sheet and a coating layer covering the surface of the first sheet;
[0009] The coating layer is made of rGO material;
[0010] The first layer comprises a MoS2@Sb2S3 heterojunction.
[0011] Optionally, the specific surface area of the MoS2@Sb2S3@rGO nanomaterial is 179–185 m².2 / g, preferably 182-184m 2 / g; and / or, the length of the rod-shaped structure is 1.2 to 2.5 μm, preferably 1.5 to 2.0 μm; and / or, the cross-sectional radius of the rod-shaped structure is 80 to 180 nm, preferably 100 to 150 nm; and / or, the length-to-length ratio of the rod-shaped structure is (8 to 18):1, preferably (12 to 16):1.
[0012] Optionally, the nanosheet diameter is 0.1–0.5 μm, preferably 0.2–0.4 μm; and / or, the nanosheet thickness is 10–30 nm, preferably 20–30 nm; the nanosheet spacing is... And / or, based on the total mass of the MoS2@Sb2S3@rGO nanomaterials, the content of the rGO material is 5-15 wt%, preferably 8-12 wt%; and / or, the thickness of the coating layer is 5-35 nm, preferably 15-30 nm.
[0013] A second aspect of the present invention provides a method for preparing a negative electrode composite material, the method comprising the following steps:
[0014] S1. The antimony source, the first sulfur source, and the rGO aqueous solution are subjected to a first mixing treatment to obtain a first mixture; the first mixture is subjected to a second mixing treatment with a template agent solution to obtain a second mixture; the pH value of the second mixture is adjusted to neutral and then subjected to a first heating treatment and a detemplating treatment to obtain the Sb2S3 / rGO composite material.
[0015] S2. Prepare a first solution containing MoS2 and a second solution containing the Sb2S3 / rGO composite material; perform a third mixing treatment on the first solution and the second solution to obtain a third mixture; perform a fourth mixing treatment and a second heating treatment on the third mixture with a soluble inorganic salt to obtain a fourth mixture; cool the fourth mixture and then filter and dry it to obtain MoS2@Sb2S3@rGO nanomaterials.
[0016] Optionally, the rGO aqueous solution contains reduced graphene oxide; preferably, the mass concentration of the reduced graphene oxide in the rGO aqueous solution is 0.1–1 mg / mL; the mass ratio of the antimony source, the first sulfur source, and the reduced graphene oxide is 1:(1.5–4):(0.01–0.1); and / or, the mass content of the template agent in the template agent solution is 5–20 wt%; and / or, the volume ratio of the first mixture to the template agent solution is (1–3):1; and / or, the mass concentration of MoS2 in the first solution is 1–10 mg / mL; and / or, the mass concentration of the Sb2S3 / rGO composite material in the second solution is 0.5–5 mg / mL; and / or, the volume ratio of the first solution to the second solution is 1:(1–3); and / or, the mass of the soluble inorganic salt is 0.01–1 g relative to each mL of the third mixture.
[0017] Optionally, the antimony source includes at least one of SbCl3, SbF, SbF3, Sb2O3, and Sb(OH)3; preferably, the antimony source is SbCl3; and / or, the first sulfur source includes at least one of sodium sulfide, thioacetamide, thiourea, sulfur powder, and sodium polysulfide; preferably, the first sulfur source is sodium sulfide; and / or, the template agent includes polyvinylpyrrolidone and / or hexadecyltrimethylammonium bromide; and / or, the soluble inorganic salt includes at least one of NaCl, KCl, LiCl, CaCl2, MgCl2, and ZnCl2; and / or, the first solution containing MoS2 contains a first solvent, the first solvent including at least one of ethanol, isopropanol, acetone, acetonitrile, and DMF; and / or, the second solution containing the Sb2S3 / rGO composite material includes a second solvent, the second solvent including at least one of dichloromethane, dichloroethane, carbon tetrachloride, chloroform, and ethyl acetate.
[0018] Optionally, in step S1, the second mixing treatment is a first ultrasonic treatment, the conditions of which include: a temperature of 20-30°C, a time of 10-30 min, and a frequency of 20-40 kHz; and / or, the conditions of the first heating treatment include: a temperature of 100-150°C, and a time of 12-18 h; and / or, the conditions of the de-templating treatment include: washing and centrifuging the material after the first heating treatment, followed by calcination; wherein the calcination is carried out in an inert atmosphere, the temperature of the calcination is 700-900°C, and the time of the calcination is 1-4 h; in step S2, the fourth mixing treatment is a second ultrasonic treatment, the conditions of which include: a temperature of 25-40°C, a time of 5-15 min, and a frequency of 25-50 kHz; and / or, the conditions of the second heating treatment include: a temperature of 140-160°C, and a time of 4-8 h.
[0019] Optionally, the preparation method further includes the preparation of MoS2; the preparation method of MoS2 includes: mixing a molybdenum source and a second sulfur source and then calcining the mixture; optionally, the mass ratio of the molybdenum source and the second sulfur source is 1:(1-4); optionally, the molybdenum source includes at least one of ammonium molybdate, sodium molybdate, potassium molybdate, calcium molybdate, and molybdenum trioxide; and / or, the second sulfur source includes sulfur powder and / or hydrogen sulfide; optionally, the calcination conditions include: a temperature of 650-950℃ and a time of 1-3h.
[0020] A third aspect of the present invention provides a negative electrode sheet comprising a negative electrode active material, wherein the negative electrode active material comprises the above-described negative electrode composite material and / or a negative electrode composite material prepared according to the above-described method.
[0021] A fourth aspect of the present invention provides a battery comprising a negative electrode sheet, wherein the negative electrode sheet is the aforementioned negative electrode sheet.
[0022] The beneficial technical effects of the present invention through the above technical solution are as follows:
[0023] (1) The MoS2@Sb2S3@rGO nanomaterial of the present invention has an overall nanorod structure. The rod structure has a relatively regular shape and orientation, which can mitigate and disperse the stress caused by volume expansion. The rod morphology makes the volume change of the material more uniform in a certain direction during charging and discharging, reducing the stress concentration inside the material and improving structural stability and cycle life. The rod structure can better connect the individual particles, reduce the barrier to electron transport, and improve the overall conductivity of the battery. The rod structure has high mechanical strength. Compared with granular or other morphological materials, the rod structure can better withstand repeated volume changes and avoid material breakage and pulverization. The rod structure has good dispersibility, avoiding the problems of particle accumulation and agglomeration.
[0024] (2) The rod-like structure of the MoS2@Sb2S3@rGO nanomaterial of the present invention is formed by stacking several nanosheets. The layered arrangement of the nanosheets shortens the diffusion path of lithium ions by increasing the interlayer spacing, thereby improving the rate performance. The nanosheets include a first layer and a coating layer covering the surface of the first layer; the coating layer is made of rGO material; the first layer includes a MoS2@Sb2S3 heterojunction. MoS2 is a semiconductor with a direct bandgap, providing abundant lithium intercalation sites, which facilitates the rapid insertion and extraction of lithium ions; Sb2S3 also provides abundant lithium intercalation sites, facilitating the rapid insertion and extraction of lithium ions. Simultaneously, Sb2S3 also possesses semiconductor properties. The two are bandgap matched, forming an effective carrier separation and transport channel at the interface, thus forming the MoS2@Sb2S3 heterojunction. The heterojunction formed by MoS2 and Sb2S3 can provide a buffering effect through the MoS2 structure, reducing the volume expansion of the Sb2S3 material. The formation of the heterojunction structure allows the composite material to fully leverage the advantages of both materials, improving the overall capacity and energy density. During the composite process, the interlayer gaps of MoS2 can provide additional lithium storage space for Sb2S3, further increasing the total battery capacity. The combination of MoS2 and Sb2S3 structures effectively improves the mechanical strength and toughness of the material, reducing the breakage or pulverization of the battery during charge and discharge. rGO (coated on the surface of MoS2@Sb2S3) has good electrical conductivity and mechanical stability, significantly improving conductivity and providing physical support during multiple charge and discharge cycles, preventing material fracture due to expansion and contraction, and improving cycle stability and lifespan.
[0025] (3) The negative electrode composite material of the present invention, as a negative electrode material for lithium-ion batteries, improves the battery capacity and energy while improving its conductivity and cycle stability.
[0026] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0027] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0028] Figure 1 The image shown is a SEM image of the negative electrode composite material prepared in Example 1 (a is a low-magnification SEM, b is a high-magnification SEM).
[0029] Figure 2 The image shown is the XRD pattern of the negative electrode composite material prepared in Example 1.
[0030] Figure 3 The image shown is a SEM image of the negative electrode composite material prepared in Comparative Example 4. Detailed Implementation
[0031] This invention discloses a negative electrode composite material and its preparation method, a negative electrode sheet, and a battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0032] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0033] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0034] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0035] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0036] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0037] To address the issues of poor conductivity and cycle stability in existing antimony-molybdenum transition metal sulfide anode materials, the present invention employs the following technical solution:
[0038] A first aspect of the present invention provides a negative electrode composite material, the negative electrode composite material comprising MoS2@Sb2S3@rGO nanomaterials; the MoS2@Sb2S3@rGO nanomaterials being a rod-shaped structure formed by stacking several nanosheets;
[0039] The nanosheet includes a first sheet and a coating layer covering the surface of the first sheet;
[0040] The coating layer is made of rGO material;
[0041] The first layer comprises a MoS2@Sb2S3 heterojunction.
[0042] The MoS2@Sb2S3@rGO nanomaterial of the present invention comprises rGO material and a MoS2@Sb2S3 heterojunction. MoS2 is a semiconductor with a direct bandgap, providing abundant lithium-ion intercalation sites, facilitating rapid lithium-ion insertion and extraction. Sb2S3 also provides abundant lithium-ion intercalation sites, facilitating rapid lithium-ion insertion and extraction, and also exhibits semiconductor properties. The two materials are bandgap matched, forming an effective carrier separation and transport channel at the interface, thus creating the MoS2@Sb2S3 heterojunction.
[0043] The MoS2@Sb2S3@rGO nanomaterials in this invention have a large specific surface area and a specific morphology, which helps to increase the contact area with the electrolyte, thereby improving the charge and discharge efficiency.
[0044] The MoS2@Sb2S3@rGO nanomaterial of this invention exhibits an overall nanorod-like structure. This rod-like structure possesses a relatively regular shape and orientation, which can mitigate and disperse the stress caused by volume expansion. The rod-like morphology allows for more uniform volume changes in a certain direction during charging and discharging, reducing internal stress concentration and improving structural stability and cycle life. The rod-like structure better connects individual particles, reducing obstacles to electron transport and improving the overall conductivity of the battery. The rod-like structure possesses high mechanical strength; compared to granular or other morphological materials, it can better withstand repeated volume changes, preventing material breakage and pulverization. The rod-like structure also exhibits good dispersibility, avoiding particle aggregation and agglomeration.
[0045] The rod-like structure of the MoS2@Sb2S3@rGO nanomaterial of this invention is formed by stacking several nanosheets. The layered arrangement of the nanosheets increases the interlayer spacing, shortening the diffusion path of lithium ions and thus improving rate performance. Each nanosheet includes a first layer and a coating layer covering the surface of the first layer; the coating layer is made of rGO material; the first layer includes a MoS2@Sb2S3 heterojunction. MoS2 is a semiconductor with a direct bandgap, providing abundant lithium intercalation sites, facilitating rapid lithium ion insertion and extraction. Sb2S3 also provides abundant lithium intercalation sites, facilitating rapid lithium ion insertion and extraction, and also possesses semiconductor properties. The two materials are band-matched, forming an effective carrier separation and transport channel at the interface, thus forming the MoS2@Sb2S3 heterojunction. The heterojunction formed by MoS2 and Sb2S3 can provide a buffering effect through the MoS2 structure, reducing the volume expansion of the Sb2S3 material. The formation of the heterojunction structure allows the composite material to fully leverage the advantages of both materials, improving the overall capacity and energy density. During the composite process, the interlayer gaps of MoS2 can provide additional lithium storage space for Sb2S3, further increasing the total battery capacity. The combination of MoS2 and Sb2S3 structures effectively improves the mechanical strength and toughness of the material, reducing the breakage or pulverization of the battery during charge and discharge. rGO (coated on the surface of MoS2@Sb2S3) has good electrical conductivity and mechanical stability, significantly improving conductivity and providing physical support during multiple charge and discharge cycles, preventing material fracture due to expansion and contraction, and improving cycle stability and lifespan.
[0046] In embodiments of the present invention, the specific surface area of the MoS2@Sb2S3@rGO nanomaterial can be 179–185 m². 2 / g, for example, the specific surface area of the MoS2@Sb2S3@rGO nanomaterial can be 179m². 2 / g、181m 2 / g、183m 2 / g and 185m 2 Any value in / g or any value within the range formed by any two of the above values. An excessively large specific surface area of the MoS2@Sb2S3@rGO nanomaterial may lead to increased surface defects, reduced mechanical stability, and increased interfacial resistance, thus reducing efficiency. Conversely, an excessively small specific surface area may result in insufficient active sites, limiting battery capacity. In a preferred embodiment of the present invention, the specific surface area of the MoS2@Sb2S3@rGO nanomaterial can be 182–184 m². 2 / g. In this embodiment, the active site density of the MoS2@Sb2S3@rGO nanomaterial is significantly improved, and the lithium-ion insertion / extraction efficiency is increased by 20% to 30%.
[0047] In this invention, the term "rod-like structure" generally refers to a linear, one-dimensional, or quasi-one-dimensional structural form in a molecule or crystal, wherein atoms or groups are arranged regularly along a certain direction, resembling the shape of a "rod." The term "rod length of a rod-like structure" is the longest diameter of the linear, one-dimensional, or quasi-one-dimensional structure. The term "radius of a cross-section of a rod-like structure" is the radius of the rod-like structure perpendicular to its length. The term "length-to-radius ratio of a rod-like structure" is the ratio of the rod length to the cross-sectional radius of the rod-like structure.
[0048] In embodiments of the present invention, the length of the rod-shaped structure can be 1.2–2.5 μm. Exemplarily, the length of the rod-shaped structure can be any value selected from 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, and 2.5 μm, or any value within the range formed by any pair of the above values. In a preferred embodiment of the present invention, the length of the rod-shaped structure can be 1.5–2.0 μm. In this embodiment, the diffusion path of lithium ions within the nanomaterial is significantly shortened, and the surface active sites are uniformly distributed.
[0049] In embodiments of the present invention, the cross-sectional radius of the rod-shaped structure can be 80–180 nm. Exemplarily, the cross-sectional radius of the rod-shaped structure can be any value selected from 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, and 180 nm, or any value within the range formed by any pair of the aforementioned values. Preferably, the cross-sectional radius of the rod-shaped structure can be 100–150 nm.
[0050] In embodiments of the present invention, the length-to-diameter ratio of the rod-shaped structure can be (8-18):1. Exemplarily, the length-to-diameter ratio can be any value from 8:1, 10:1, 12:1, 14:1, 16:1, and 18:1, or any value within the range formed by any two of the above values. If the length-to-diameter ratio of the rod-shaped structure is too large, it may lead to poor mechanical stability of the nanorods, making them prone to bending or breakage; if the length-to-diameter ratio of the rod-shaped structure is too small, it will also reduce the specific surface area, potentially resulting in low lithium storage performance of the battery. Preferably, the length-to-diameter ratio of the rod-shaped structure can be (12-16):1. More preferably, when the short-diameter ratio is 14:1, the diffusion rate of lithium ions along the long axis of the rod-shaped structure is three times that in the radial direction, significantly reducing polarization.
[0051] In embodiments of the present invention, the diameter of the nanosheet can be 0.1–0.5 μm. Exemplarily, it can be any value selected from 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, and 0.5 μm, or any value within the range formed by any pair of the above values. If the diameter of the nanosheet is too small, it may lead to nanosheet aggregation, reducing ion transport efficiency; if the diameter of the nanosheet is too large, it reduces the specific surface area of the active material. Preferably, the diameter of the nanosheet can be 0.2–0.4 μm.
[0052] In embodiments of the present invention, the thickness of the nanosheet can be 10–30 nm. Exemplarily, the thickness of the nanosheet can be any value selected from 10 nm, 15 nm, 20 nm, 25 nm, and 30 nm, or any value within the range formed by any pair of the above values. If the nanosheet is too thin, it may reduce the mechanical strength of the material; if the nanosheet is too thick, it will prolong the diffusion path of lithium ions. Preferably, the thickness of the nanosheet can be 20–30 nm.
[0053] In embodiments of the present invention, excessively large interlayer spacing leads to a loose material structure, reduced mechanical strength, and impaired cycling performance. It also increases electron transport paths, reduces electrical conductivity, and increases electrolyte penetration, potentially causing interfacial side reactions. Conversely, excessively small interlayer spacing makes lithium-ion insertion and extraction difficult, resulting in decreased kinetic performance. Too small an interlayer spacing fails to provide sufficient lithium insertion space, limiting specific capacity. The interlayer spacing of the nanosheets described in this invention can be... For example, the interlayer spacing of the nanosheets can be... and Any value in the range or any value within the range formed by any pair of the above values.
[0054] In embodiments of the present invention, the content of rGO material can be 5–15 wt%, based on the total mass of the MoS2@Sb2S3@rGO nanomaterials. Exemplarily, the content of rGO material can be any value from 5 wt%, 7 wt%, 9 wt%, 12 wt%, and 15 wt%, or any value within the range of any pair of values mentioned above, based on the total mass of the MoS2@Sb2S3@rGO nanomaterials. If the content of rGO material is too low, an effective three-dimensional conductive network cannot be formed, leading to increased polarization; if the content of rGO material is too high, the proportion of active material will be diluted, reducing the theoretical capacity. Preferably, the content of rGO material can be 8–12 wt%, based on the total mass of the MoS2@Sb2S3@rGO nanomaterials.
[0055] In embodiments of the present invention, the thickness of the coating layer can be 5–35 nm. Exemplarily, the thickness of the coating layer can be any value selected from 5 nm, 10 nm, 20 nm, 25 nm, and 35 nm, or any value within the range formed by any pair of the aforementioned values. Preferably, the thickness of the coating layer can be 15–30 nm, which allows for the formation of a dense rGO protective layer, reducing side reactions in the electrolyte.
[0056] A second aspect of the present invention provides a method for preparing a negative electrode composite material, the method comprising the following steps:
[0057] S1. The antimony source, the first sulfur source, and the rGO aqueous solution are subjected to a first mixing treatment to obtain a first mixture; the first mixture is subjected to a second mixing treatment with a template agent solution to obtain a second mixture; the pH value of the second mixture is adjusted to 7 and then subjected to a first heating treatment and a detemplating treatment to obtain the Sb2S3 / rGO composite material.
[0058] S2. Prepare a first solution containing MoS2 and a second solution containing the Sb2S3 / rGO composite material; perform a third mixing treatment on the first solution and the second solution to obtain a third mixture; perform a fourth mixing treatment and a second heating treatment on the third mixture with a soluble inorganic salt to obtain a fourth mixture; cool the fourth mixture and then filter and dry it to obtain MoS2@Sb2S3@rGO nanomaterials.
[0059] In an embodiment of the present invention, the rGO aqueous solution contains reduced graphene oxide; preferably, the mass concentration of the reduced graphene oxide in the rGO aqueous solution can be 0.1 to 1 mg / mL.
[0060] In embodiments of the present invention, the mass ratio of the antimony source, the first sulfur source, and the reduced graphene oxide can be 1:(1.5-4):(0.01-0.1). In this invention, if the proportion of the antimony source is too large, it leads to incomplete reaction, generating excess byproducts and reducing the purity of the material. Excessive antimony source will form a large number of particles or agglomerated structures, which cannot effectively bind with rGO. If the proportion of the antimony source is too small, the Sb2S3 product is insufficient, resulting in a low antimony content in the composite material and reducing the specific capacity of the composite material. Furthermore, the surface of rGO cannot be fully utilized, limiting the growth of Sb2S3 nanostructures and affecting the performance of the composite material. If the proportion of the first sulfur source is too large, it leads to over-reaction, generating a large number of polysulfide byproducts; if the proportion of the first sulfur source is too small, it leads to incomplete Sb2S3 growth or the formation of other antimony compounds. If the proportion of GO is too large, it will cause the surface of rGO in the composite material to be saturated, reducing the growth space of Sb2S3, and may also cause rGO itself to agglomerate, resulting in poor conductivity of the composite material. If the proportion of GO is too small, it cannot provide enough support and dispersion for Sb2S3, making it difficult for Sb2S3 to be evenly distributed on the surface of rGO. If there is too little rGO, the conductivity will be poor, affecting the electrical conductivity of the material.
[0061] In embodiments of the present invention, the template agent solution contains a template agent content of 5 to 20 wt%. For example, the template agent solution contains a template agent content of any one of 5 wt%, 8 wt%, 10 wt%, 15 wt%, and 20 wt%, or any value within the range of any two of the above values.
[0062] In embodiments of the present invention, the volume ratio of the first mixture to the template agent solution can be (1-3):1. Exemplarily, the volume ratio of the first mixture to the template agent solution can be any value from 1:1, 1.5:1, 2:1, 2.5:1, and 3:1, or any value within the range of any two of the above values. In this invention, if the proportion of the template agent solution is too small, it cannot effectively provide sufficient template action, resulting in a relatively free morphology of the synthesized Sb₂S₃, leading to an unstable nanostructure with poor uniformity. If the proportion of the template agent solution is too large, it increases the solution viscosity, making molecules more prone to aggregation and causing particle aggregation; excessive amounts can lead to the formation of other non-rod structures.
[0063] In embodiments of the present invention, the mass concentration of MoS2 in the first solution can be 1–10 mg / mL. A suitable mass concentration of MoS2 can enable the synthesized MoS2 to possess both a certain thickness and deposition efficiency. Exemplarily, the mass concentration of MoS2 in the first solution can be any value selected from 1 mg / mL, 2 mg / mL, 4 mg / mL, 5 mg / mL, 8 mg / mL, and 10 mg / mL, or any value within the range formed by any pair of the above values.
[0064] In embodiments of the present invention, the mass concentration of the Sb₂S₃ / rGO composite material in the second solution can be 0.5–5 mg / mL. This concentration ensures that rGO can effectively form a mixture with Sb₂S₃, guaranteeing the homogeneity of the solution. Exemplarily, the mass concentration of the Sb₂S₃ / rGO composite material in the second solution can be any value selected from 0.5 mg / mL, 2 mg / mL, 4 mg / mL, and 5 mg / mL, or any value within the range formed by any pair of the aforementioned values.
[0065] In embodiments of the present invention, the volume ratio of the first solution to the second solution can be 1:(1 to 3). For example, the volume ratio of the first solution to the second solution can be any value among 1:1, 1:1.5, 1:2, 1:2.5, and 1:3, or any value within the range of any two of the above values.
[0066] In embodiments of the present invention, the mass of the soluble inorganic salt relative to each mL of the third mixture can be 0.01 to 1 g. Exemplarily, the mass of the soluble inorganic salt relative to each mL of the third mixture can be any value selected from 0.01 g, 0.1 g, 0.5 g, 0.8 g, and 1 g, or any value within the range formed by any pair of the above values.
[0067] For example, the antimony source may include at least one of SbCl3, SbF, SbF3, Sb2O3, and Sb(OH)3; preferably, the antimony source is SbCl3. SbCl3 has high solubility and readily reacts with sulfur sources to form Sb2S3. By adjusting the concentration of SbCl3, the formation of Sb2S3 during the synthesis process can be easily controlled.
[0068] For example, the first sulfur source may include at least one of sodium sulfide, thioacetamide, thiourea, sulfur powder, and sodium polysulfide; preferably, the first sulfur source is sodium sulfide. Sodium sulfide is a commonly used, stable, and controllable sulfur source with mild reaction conditions and high solubility. Compared to other sulfur sources, such as hydrogen sulfide or carbon disulfide, sodium sulfide is easier to control and the reaction conditions are milder.
[0069] For example, the template agent may include polyvinylpyrrolidone and / or hexadecyltrimethylammonium bromide.
[0070] In this invention, the addition of soluble inorganic salts can alter the conductivity of the mixed solution, promoting the directional growth of materials to form macroscopic nanorod structures. Exemplarily, the soluble inorganic salts may include at least one of NaCl, KCl, LiCl, CaCl2, MgCl2, and ZnCl2.
[0071] In some embodiments, the first solution containing MoS2 may contain a first solvent. Exemplarily, the first solvent may include at least one of ethanol, isopropanol, acetone, acetonitrile, and DMF.
[0072] In some embodiments, the second solution containing the Sb2S3 / rGO composite material includes a second solvent, which, exemplarily, may include at least one of dichloromethane, dichloroethane, carbon tetrachloride, chloroform, and ethyl acetate.
[0073] In some embodiments, in step S1, the second mixing process is a first ultrasonic process, and the conditions of the first ultrasonic process include: a temperature of 20 to 30°C, a time of 10 to 30 minutes, and a frequency of 20 to 40 kHz.
[0074] In some embodiments, in step S1, the conditions for the first heat treatment may include: a temperature of 100–150°C and a time of 12–18 hours. In this invention, if the first heat treatment temperature is too low or the time is too short, the reaction kinetics may be insufficient, and the material may not crystallize completely; if the first heat treatment temperature is too high or the time is too long, it may lead to the pyrolysis or carbonization of polyvinylpyrrolidone (PVP), resulting in morphological damage.
[0075] In some embodiments, in step S1, the conditions for the destenosis treatment may include: washing and centrifuging the material after the first heating treatment and then calcining it; wherein, washing and centrifuging may include: washing with deionized water / ethanol 3-5 times to remove unreacted PVP; the calcination treatment is carried out in an inert atmosphere, the temperature of the calcination treatment is 700-900°C, and the time of the calcination treatment is 1-4 hours.
[0076] In some embodiments, in step S2, the fourth mixing treatment is a second ultrasonic treatment, the conditions of which include: a temperature of 25-40°C, a time of 5-15 min, and a frequency of 25-50 kHz; and / or, the conditions of the second heating treatment include: a temperature of 140-160°C, and a time of 4-8 h.
[0077] In some embodiments, the preparation method further includes the preparation of MoS2; the preparation method of MoS2 includes: mixing a molybdenum source and a second sulfur source and then calcining the mixture; optionally, the mass ratio of the molybdenum source to the second sulfur source is 1:(1-4). In this invention, if the proportion of molybdenum source is too large, it will lead to insufficient sulfur source, residual molybdenum oxide, and affect the crystallinity of MoS2; too much molybdenum source will cause MoS2 to grow or form other undesirable phases, affecting the uniformity of MoS2; if the molybdenum source is too small, the sulfur will be excessive, resulting in a less uniform MoS2 or the formation of various sulfides, affecting the purity and quality of MoS2; optionally, the molybdenum source includes at least one of ammonium molybdate, sodium molybdate, potassium molybdate, calcium molybdate, and molybdenum trioxide; and / or, the second sulfur source includes sulfur powder and / or hydrogen sulfide; optionally, the calcination conditions include: a temperature of 650-950°C and a time of 1-3 hours. In some embodiments, calcination is carried out under the action of a protective gas, which includes at least one of nitrogen and argon.
[0078] In some embodiments, the preparation method further includes the preparation of rGO and template agent solutions.
[0079] For example, the preparation method of rGO includes: preparing graphene (GO) using the Hummer method, adding a reducing agent to an aqueous solution of GO, and obtaining reduced graphene oxide (rGO) through a reduction reaction at room temperature. The Hummer method for preparing graphene can be as follows: first, high-purity natural graphite powder and concentrated sulfuric acid (H2SO4) are mixed at a mass ratio of 1:50, and vigorously stirred in an ice bath (0-5℃) until a homogeneous colloid is formed. Then, potassium permanganate (KMnO4) is slowly added until the total mass ratio is graphite:sulfuric acid:potassium permanganate = 1:50:10, strictly controlling the reaction temperature ≤20℃ to avoid violent exothermic reactions that could lead to danger. After continuous stirring for 24 hours, oxygen-containing functional groups (such as hydroxyl and carboxyl groups) are fully intercalated between the graphite layers, forming brownish-black graphene oxide (GO). Next, deionized water is added to dilute the system and the temperature is raised to 98℃. Then, 30% hydrogen peroxide (H2O2) is added dropwise to decompose the remaining potassium permanganate, terminating the strong oxidation reaction. After centrifugation, the product is repeatedly washed with dilute hydrochloric acid and deionized water until neutral (pH=7), and then dried to obtain graphene oxide powder. GO is dispersed in water or solvents such as N-methylpyrrolidone (NMP) and exfoliated into single-layer or few-layer graphene oxide by ultrasonic treatment (500W, 1-2 hours). The reducing agent may include one or more of sodium hydride, sodium hydroxide, and hydrazine hydrate. In the GO aqueous solution, the mass percentage of GO is 0.5-2 wt%; the mass ratio of GO to reducing agent is (1-5):1.
[0080] For example, the template agent solution is prepared by adding the template agent to water and heating and stirring (60-80℃, 30-60 min) to obtain the template agent solution. The template agent accounts for 5-20 wt% of the template agent solution.
[0081] A third aspect of the present invention provides a negative electrode sheet comprising a negative electrode active material, wherein the negative electrode active material comprises the above-described negative electrode composite material and / or a negative electrode composite material prepared according to the above-described method.
[0082] A fourth aspect of the present invention provides a battery comprising a negative electrode sheet, wherein the negative electrode sheet is the aforementioned negative electrode sheet.
[0083] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0084] Example 1
[0085] (1) Preparation of rGO aqueous solution and template agent solution
[0086] Preparation of rGO aqueous solution and template agent solution: GO aqueous solution was prepared by Hummer method, with a GO mass ratio of 1 wt% (1 g GO, 99 g deionized water). 3 g hydrazine hydrate was added to the GO aqueous solution, and a reduction reaction was carried out at room temperature to obtain reduced graphene oxide aqueous solution (rGO aqueous solution). 5 g polyvinylpyrrolidone (PVP) was added to 45 g water, heated and stirred at 70 °C for 40 min to obtain PVP template agent solution.
[0087] (2) Preparation of Sb2S3 / rGO composite material
[0088] 2g of antimony chloride and 6g of sodium sulfide were dissolved in an rGO aqueous solution (GO content 0.2g) to obtain a first mixture. 40mL of the first mixture and 20mL of PVP template agent solution were mixed and subjected to a first ultrasonic treatment (temperature 25℃, time 20min, frequency 40kHz) until homogeneous, resulting in a second mixture. The pH of the second mixture was adjusted to neutral (pH=7), and a first heat treatment and detemplating treatment were performed. Detemplating yielded the Sb2S3 / rGO composite material. The first heat treatment was performed at 120℃ for 15h. The detemplating step included: firstly, the product after the first heat treatment was centrifuged and washed three times with deionized water to remove unreacted PVP, and then calcined at 800℃ for 2h in an inert atmosphere.
[0089] 2g of sodium molybdate and 6g of sulfur powder were thoroughly mixed and annealed at 800℃ for 2 hours in a tube furnace to obtain MoS2. 0.2g of MoS2 was dispersed in 50mL of ethanol to obtain a first solution, and 0.1g of the Sb2S3 / rGO composite material was dispersed in 50mL of dichloromethane to obtain a second solution. The first and second solutions were mixed to obtain a third mixture. The prepared third mixture was mixed with 1g of NaCl inorganic salt and subjected to a second ultrasonic treatment and a second heat treatment. The conditions for the second ultrasonic treatment were: time 1 hour, temperature 25℃, frequency 40kHz; the conditions for the second heat treatment were: temperature 150℃, time 6 hours. After the second heat treatment, the material was cooled, filtered, solvent removed, and dried to obtain the nanorod-shaped MoS2@Sb2S3@rGO composite material of this embodiment.
[0090] Example 2
[0091] (1) Preparation of rGO aqueous solution and template agent solution
[0092] Preparation of rGO aqueous solution and template agent solution: GO aqueous solution was prepared using the Hummer method, with a GO mass ratio of 0.5 wt% (0.5 g GO, 99.5 g deionized water). 2.5 g of hydrazine hydrate was added to the GO aqueous solution, and a reduction reaction was carried out at room temperature to obtain reduced graphene oxide aqueous solution (rGO aqueous solution). 2.5 g of polyvinylpyrrolidone (PVP) was added to 47.5 g of water, and the mixture was heated and stirred at 60 °C for 30 min to obtain the PVP template agent solution.
[0093] (2) Preparation of Sb2S3 / rGO composite material
[0094] 2g of antimony chloride and 3g of sodium sulfide were dissolved in an rGO aqueous solution (GO content 0.2g) to obtain a first mixture. 40mL of the first mixture and 40mL of PVP template agent solution were mixed and subjected to a first ultrasonic treatment (temperature 25℃, time 20min, frequency 30kHz) until homogeneous, resulting in a second mixture. The pH of the second mixture was adjusted to 6.5, followed by a first heat treatment and a detemplating treatment. Detemplating yielded the Sb2S3 / rGO composite material. The first heat treatment was performed at 100℃ for 12h. The detemplating step included: firstly, the product after the first heat treatment was centrifuged and washed three times with deionized water to remove unreacted PVP, and then calcined at 800℃ for 2h in an inert atmosphere.
[0095] 2g of sodium molybdate and 2g of sulfur powder were thoroughly mixed and annealed at 650℃ for 1 hour in a tube furnace to obtain MoS2. 0.05g of MoS2 was dispersed in 50mL of ethanol to obtain a first solution, and 0.025g of Sb2S3 / rGO composite material was dispersed in 50mL of dichloromethane to obtain a second solution. The first and second solutions were mixed to obtain a third mixture. The prepared third mixture was mixed with 1g of NaCl inorganic salt and subjected to a second ultrasonic treatment and a second heat treatment. The conditions for the second ultrasonic treatment were: time 1 hour, temperature 25℃, frequency 40kHz; the conditions for the second heat treatment were: temperature 140℃, time 4 hours. After the second heat treatment, the material was cooled, filtered, solvent removed, and dried to obtain the nanorod-shaped MoS2@Sb2S3@rGO composite material of this embodiment.
[0096] Example 3
[0097] (1) Preparation of rGO aqueous solution and template agent solution
[0098] Preparation of rGO aqueous solution and template agent solution: GO aqueous solution was prepared using the Hummer method, with a GO mass ratio of 2wt% (2g GO, 98g deionized water). 2g of hydrazine hydrate was added to the GO aqueous solution, and a reduction reaction was carried out at room temperature to obtain reduced graphene oxide aqueous solution (rGO aqueous solution). 10g of polyvinylpyrrolidone (PVP) was added to 40g of water, and the mixture was heated and stirred at 80℃ for 60min to obtain the PVP template agent solution.
[0099] (2) Preparation of Sb2S3 / rGO composite material
[0100] 2g of antimony chloride and 8g of sodium sulfide were dissolved in an rGO aqueous solution (GO content 0.2g) to obtain a first mixture. 60mL of the first mixture and 20mL of PVP template agent solution were mixed and subjected to a first ultrasonic treatment (temperature 25℃, time 20min, frequency 30kHz) until homogeneous, resulting in a second mixture. The pH of the second mixture was adjusted to 7.5, followed by a first heat treatment and a detemplation treatment to obtain the Sb2S3 / rGO composite material. The first heat treatment was performed at 150℃ for 18h. The detemplation step included: firstly, the product after the first heat treatment was centrifuged and washed three times with deionized water to remove unreacted PVP, and then calcined at 800℃ for 2h in an inert atmosphere.
[0101] 2g of sodium molybdate and 8g of sulfur powder were thoroughly mixed and annealed at 950℃ for 3h in a tube furnace to obtain MoS2. 0.5g of MoS2 was dispersed in 50mL of ethanol to obtain a first solution, and 0.25g of Sb2S3 / rGO composite material was dispersed in 50mL of dichloromethane to obtain a second solution. The first and second solutions were mixed to obtain a third mixture. The prepared third mixture was mixed with 5g of NaCl inorganic salt and subjected to a second ultrasonic treatment and a second heat treatment. The conditions for the second ultrasonic treatment were: time 1h, temperature 25℃, frequency 40kHz; the conditions for the second heat treatment were: temperature 160℃, time 8h. After the second heat treatment, the material was cooled, filtered, solvent removed, and dried to obtain the nanorod-shaped MoS2@Sb2S3@rGO composite material of this embodiment.
[0102] Example 4
[0103] The preparation method of the MoS2@Sb2S3@rGO composite material in this embodiment is the same as that in Example 1, except that PVP is replaced with hexadecyltrimethylammonium bromide (CTAB).
[0104] Example 5
[0105] The preparation method of the MoS2@Sb2S3@rGO composite material in this embodiment is the same as that in Example 1, except that NaCl inorganic salt is replaced with KCl inorganic salt.
[0106] Example 6
[0107] The preparation method of the MoS2@Sb2S3@rGO composite material in this embodiment is the same as that in Embodiment 1, except that the antimony source in this embodiment is antimony fluoride.
[0108] Example 7
[0109] The preparation method of the MoS2@Sb2S3@rGO composite material in this embodiment is the same as that in Example 1, except that the first sulfur source in this embodiment is thioacetamide.
[0110] Example 8
[0111] The preparation method of the MoS2@Sb2S3@rGO composite material in this embodiment is the same as that in Example 1, except that the molybdenum source used in this embodiment is ammonium molybdate.
[0112] Example 9
[0113] The preparation method of the MoS2@Sb2S3@rGO composite material in this embodiment is the same as that in Embodiment 1, except that the second sulfur source in this embodiment is hydrogen sulfide.
[0114] Comparative Example 1
[0115] Preparation scheme of MoS2@rGO nanocomposite material: A 1wt% GO aqueous solution (1g GO + 99g deionized water) was prepared according to the Hummers method. 3g hydrazine hydrate was added to the GO solution, and a reduction reaction was carried out at room temperature to generate an rGO aqueous solution. 2g sodium molybdate and 6g sulfur powder were mixed and annealed in a tube furnace at 800℃ for 2h to obtain MoS2 powder. 0.2g MoS2 was dispersed in 50mL ethanol and sonicated at 40kHz for 1h at 25℃ to obtain the first solution. The rGO aqueous solution (containing 0.2g GO) was directly used as the second solution (the Sb2S3 / rGO preparation step is omitted). The first and second solutions were mixed, 1g NaCl was added, and the mixture was sonicated (40kHz for 1h at 25℃). The mixture was transferred to a reaction vessel, heated at 150℃ for 6h, cooled, filtered, washed, and dried to obtain the MoS2@rGO composite material.
[0116] Comparative Example 2
[0117] Preparation scheme of Sb2S3@rGO composite material: Hummers oxidation method: 1g GO was dispersed in 99g deionized water to prepare a 1wt% GO aqueous solution. Reduction reaction: 3g hydrazine hydrate was added to the GO solution, and the mixture was stirred at room temperature for 24h to obtain an rGO aqueous solution (concentration 0.2g GO / L). 2g SbCl3 and 6g Na2S were dissolved in the rGO aqueous solution (containing 0.2g GO), and ultrasonically dispersed (40kHz, 20min, 25℃) to obtain the first mixture. 20mL PVP solution (concentration 10wt%, 5g PVP + 45g deionized water) was added, and ultrasonication was continued for 1h until homogeneous. The pH of the mixture was adjusted to 7, and the mixture was transferred to a reactor and heated at 120℃ for 15h to form the Sb2S3 / rGO precursor. The product was centrifuged and washed 3 times (with deionized water), and calcined at 800℃ under an inert atmosphere for 2h to remove PVP, yielding the Sb2S3@rGO composite material.
[0118] Comparative Example 3
[0119] Preparation scheme of MoS2@Sb2S3 composite material: Dissolve 2g SbCl3 and 6g Na2S in 40mL deionized water and ultrasonically disperse (40kHz, 20min, 25℃) until completely dissolved. Adjust pH to 7, heat at 120℃ for 15h, cool, centrifuge and wash 3 times (with deionized water), and calcine at 800℃ for 2h to remove residual reagents, obtaining Sb2S3 powder. Mix 2g sodium molybdate with 6g sulfur powder and anneal in a tube furnace at 800℃ for 2h to obtain MoS2 powder. Disperse 0.2g MoS2 in 50mL ethanol and ultrasonically treat (40kHz, 1h, 25℃) to obtain the first solution. Disperse 0.1g Sb2S3 in 50mL dichloromethane and ultrasonically treat (40kHz, 1h, 25℃) to obtain the second solution. Mix the first and second solutions, add 1g NaCl, and ultrasonically disperse (40kHz, 1h, 25℃). The mixture was transferred to a reactor, heated at 150°C for 6 hours, cooled, filtered, washed, and dried to obtain the MoS2@Sb2S3 composite material.
[0120] Comparative Example 4
[0121] MoS2@Sb2S3 / rGO nanocomposites were prepared using a conventional hydrothermal method with a molybdenum source, a sulfur source, and a rGO mixed solution.
[0122] GO was ultrasonically dispersed in a solution of sodium molybdate and thiourea (mass ratio of sodium molybdate, thiourea, and GO = 1:3:0.1). SbCl3 solution was added, and the mixture was stirred until homogeneous to obtain a homogeneous solution. The solution was transferred to a reaction vessel (reaction temperature 165℃, reaction time 8 h), washed, and dried to obtain tightly bound MoS2@Sb2S3@rGO nanostructures.
[0123] Comparative Example 5
[0124] MoS2@Sb2S3@rGO nanocomposite material was obtained by high-temperature vulcanization of Sb2MoO6@rGO.
[0125] 0.62 g of ammonium molybdate was dissolved in 25 ml of GO aqueous solution (GO concentration 1 mg / ml) to prepare the first solution, and 0.456 g of antimony chloride was dissolved in 10 ml of ethanol to prepare the second solution. The two solutions were thoroughly mixed, and the mixture was subjected to hydrothermal treatment (160 °C, 36 h). After washing and drying, the Sb₂MoO₆@rGO composite material was synthesized. 0.2 g of the synthesized Sb₂MoO₆@rGO composite material was thoroughly mixed with 0.6 g of sulfur powder and heated in a tube furnace at 500 °C for 2 h (heating rate 5 °C / min) under nitrogen protection. After cooling, the MoS₂@Sb₂S₃@rGO composite material was obtained.
[0126] Test Example 1
[0127] The negative electrode composite materials prepared in the examples and comparative examples were measured. The specific surface area of the materials was measured using a nitrogen adsorption-desorption analyzer (model BETA201B) manufactured by Beijing Guance Co., Ltd. The rod length, cross-sectional radius, aspect ratio, interlayer spacing, nanosheet diameter, nanosheet thickness, and coating layer thickness were determined using SEM images. The rGO content in the materials (based on the total mass of the negative electrode composite material) was determined using energy-dispersive X-ray spectroscopy (EDS). The test results are shown in Table 1.
[0128] The SEM image of the negative electrode composite material prepared in Example 1 is shown below. Figure 1 As shown (a is a low-magnification SEM, b is a high-magnification SEM), the XRD pattern of the negative electrode composite material prepared in Example 1 is as follows. Figure 2 As shown, the SEM image of the negative electrode composite material prepared in Comparative Example 4 is as follows. Figure 3 As shown.
[0129] Table 1
[0130]
[0131]
[0132] Test Example 2
[0133] The negative electrode composite materials, conductive carbon black, and PVDF prepared in Examples 1-9 and Comparative Examples 1-5 were mixed in a mass ratio of 8:1:1. Using NMP as a solvent, the mixture was thoroughly ground into a slurry. This slurry was then evenly coated onto aluminum foil using a scraper. The slurry was cut into small circular pieces with a diameter of 14.5 mm, compacted, and used as the negative electrode. A lithium sheet was used as the positive electrode. Battery assembly was completed in a glove box. The assembly order was: negative electrode shell, negative electrode sheet, separator, positive electrode sheet, gasket, spring, positive electrode shell. Electrolyte (ethylene carbonate, dimethyl carbonate, and other organic solvents in a 1:1 volume ratio) was dripped onto both sides of the separator. Finally, the mixture was sealed to form a coin cell.
[0134] The performance of the prepared coin cells was tested, and the test results are shown in Table 2.
[0135] Cyclic performance: Tested using a blue electric shock tester, 1Ag -1 Charge to 3V using a constant current density, let stand for 30 minutes, discharge to 0.01V using a constant current density (record the initial discharge specific capacity C1), let stand for 30 minutes, and cycle 1000 times (record the discharge specific capacity C on the 1000th cycle). 1000 The capacity retention rate C was measured. 1000 / C1×100%.
[0136] Formula for calculating capacity retention:
[0137] Capacity retention rate (%) = (C n / C1)×100
[0138] C1: Initial cycle discharge specific capacity (mAh / g)
[0139] C n Specific capacity of discharge in the nth cycle
[0140] Charge / discharge performance: tested with a blue electrode tester at 0.1Ag. -1 The current density was constant-current charged to 3V, left to stand for 30 minutes, then constant-current discharged to 0.01V, left to stand for 30 minutes, and the cycle was repeated 3 times. The discharge specific capacity at the second discharge to 0.01V was recorded.
[0141] Charge transfer impedance: The Nyquist plot is obtained by measuring the impedance response of the electrode system in an electrochemical workstation by applying a small-amplitude sinusoidal wave perturbation (frequency range: 100 kHz - 10 MHz). The plot includes a semicircle in the high-frequency region, reflecting the charge transfer impedance (R0). ct The diagonal lines in the low-frequency region correspond to the diffusion control process.
[0142] Table 2
[0143]
[0144]
[0145] As shown in Tables 1 and 2, the anode composite materials prepared in Examples 1-9 possess an ordered nanorod structure and exhibit good discharge specific capacity and capacity retention in performance tests. Furthermore, the anode composite materials prepared in Examples 1-9 show significantly reduced impedance. In Examples 6-9, some materials were replaced, resulting in a slight decrease in discharge specific capacity and capacity retention, and a slight increase in impedance. The anode composite material in Comparative Example 1 does not contain Sb₂S₃, thus losing the heterojunction bimetallic synergistic lithium storage effect, and its specific surface area decreased by 25% (137 m² / g). 2 The interlayer spacing decreased by 6%. The discharge specific capacity and capacity retention rate decreased significantly, while the impedance increased significantly. The negative electrode composite material in Comparative Example 2 lacked MoS2, thus lacking a two-dimensional conductive network and having excessively small interlayer spacing. The specific surface area decreased by approximately 32%, resulting in a significant decrease in discharge specific capacity and capacity retention, and a significant increase in impedance. Comparative Example 3's negative electrode composite material lacked rGO, leading to loss of conductivity, a lack of conductive framework, and instability at the purely mechanical mixing interface. This resulted in a 420% increase in impedance and a 27% decrease in capacity retention after 1000 cycles. Comparative Example 4 used a conventional hydrothermal method to prepare the negative electrode composite material. The resulting material's disordered structure led to continuous SEI growth, resulting in an 18% decrease in interlayer spacing. Specific surface area decreased by 31% (125m²) 2 / g), the discharge specific capacity decreased by 20%, and the impedance increased by 271%. Comparative Example 5 used a high-temperature sulfidation method to prepare the negative electrode composite material without using a template agent, forming a nanosheet structure. The material deposition resulted in a relatively loose structure, lower specific surface area and ion conduction efficiency, and a 4.5% decrease in interlayer spacing. Specific surface area decreased by 81.9% (33m²) 2 / g), the discharge specific capacity decreased by 18.8%.
[0146] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode composite material, characterized in that, The preparation method includes the following steps: S1. The antimony source, the first sulfur source, and the rGO aqueous solution are subjected to a first mixing treatment to obtain a first mixture; the first mixture is subjected to a second mixing treatment with a template agent solution to obtain a second mixture; the pH value of the second mixture is adjusted to neutral and then subjected to a first heating treatment and a detemplating treatment to obtain the Sb2S3 / rGO composite material. S2. Prepare a first solution containing MoS2 and a second solution containing the Sb2S3 / rGO composite material; perform a third mixing treatment on the first solution and the second solution to obtain a third mixture; perform a fourth mixing treatment and a second heating treatment on the third mixture with a soluble inorganic salt to obtain a fourth mixture; cool the fourth mixture and then filter and dry it to obtain MoS2@Sb2S3@rGO nanomaterials; The conditions for the first heat treatment include: a temperature of 100~150℃ and a time of 12~18h; The conditions for the second heat treatment include: a temperature of 140~160℃ and a time of 4~8h.
2. The preparation method according to claim 1, characterized in that, The rGO aqueous solution contains reduced graphene oxide; and / or, In the template agent solution, the mass content of the template agent is 5~20wt%; and / or, The volume ratio of the first mixture to the template agent solution is (1~3):1; and / or, In the first solution, the mass concentration of MoS2 is 1~10 mg / mL; and / or, In the second solution, the mass concentration of the Sb₂S₃ / rGO composite material is 0.5~5 mg / mL; and / or, The volume ratio of the first solution to the second solution is 1:(1~3); and / or, The mass of the soluble inorganic salt is 0.01 to 1 g per mL of the third mixture.
3. The preparation method according to claim 2, characterized in that, In the rGO aqueous solution, the mass concentration of the reduced graphene oxide is 0.1~1 mg / mL; the mass ratio of the antimony source, the first sulfur source and the reduced graphene oxide is 1:(1.5~4):(0.01~0.1).
4. The preparation method according to claim 1, characterized in that, The antimony source includes at least one selected from SbCl3, SbF, SbF3, Sb2O3, and Sb(OH)3; and / or, The first sulfur source includes at least one of sodium sulfide, thioacetamide, thiourea, sulfur powder, and sodium polysulfide; and / or, The template agent comprises polyvinylpyrrolidone and / or hexadecyltrimethylammonium bromide; and / or, The soluble inorganic salt includes at least one selected from NaCl, KCl, LiCl, CaCl2, MgCl2, and ZnCl2; and / or, The first solution containing MoS2 contains a first solvent, which includes at least one of ethanol, isopropanol, acetone, acetonitrile, and DMF; and / or, The second solution containing the Sb2S3 / rGO composite material includes a second solvent, which includes at least one of dichloromethane, dichloroethane, carbon tetrachloride, chloroform, and ethyl acetate.
5. The preparation method according to claim 4, characterized in that, The antimony source is SbCl3.
6. The preparation method according to claim 4, characterized in that, The first sulfur source is sodium sulfide.
7. The preparation method according to claim 1, characterized in that, In step S1, the second mixing treatment is a first ultrasonic treatment, the conditions of which include: a temperature of 20~30℃, a time of 10~30min, and a frequency of 20~40kHz; and / or, the conditions of the detemplation treatment include: washing and centrifuging the material after the first heating treatment and then calcining it; wherein the calcination is carried out in an inert atmosphere, the temperature of the calcination is 700~900℃, and the time of the calcination is 1~4h; In step S2, the fourth mixing process is a second ultrasonic process, and the conditions of the second ultrasonic process include: temperature of 25~40℃, time of 5~15min, and frequency of 25~50kHz.
8. The preparation method according to claim 1, characterized in that, The preparation method also includes the preparation of MoS2; the preparation method of MoS2 includes: mixing a molybdenum source and a second sulfur source and then calcining them.
9. The preparation method according to claim 8, characterized in that, The mass ratio of the molybdenum source to the second sulfur source is 1:(1~4).
10. The preparation method according to claim 8, characterized in that, The molybdenum source includes at least one of ammonium molybdate, sodium molybdate, potassium molybdate, calcium molybdate, and molybdenum trioxide; and / or, the second sulfur source includes sulfur powder and / or hydrogen sulfide.
11. The preparation method according to claim 8, characterized in that, The calcination conditions include a temperature of 650~950℃ and a time of 1~3h.
12. A negative electrode composite material, characterized in that, The negative electrode composite material is prepared by the preparation method according to any one of claims 1 to 11.
13. The negative electrode composite material according to claim 12, characterized in that, The negative electrode composite material includes MoS2@Sb2S3@rGO nanomaterials; the MoS2@Sb2S3@rGO nanomaterials are rod-shaped structures formed by stacking several nanosheets. The nanosheet includes a first sheet and a coating layer covering the surface of the first sheet; The coating layer is made of rGO material; The first layer comprises a MoS2@Sb2S3 heterojunction.
14. The negative electrode composite material according to claim 13, characterized in that, The specific surface area of the MoS2@Sb2S3@rGO nanomaterial is 179~185m². 2 / g; and / or, The rod-shaped structure has a rod length of 1.2~2.5μm; and / or, The cross-sectional radius of the rod-shaped structure is 80~180 nm; and / or, The length-to-length ratio of the rod-shaped structure is (8~18):
1.
15. The negative electrode composite material according to claim 14, characterized in that, The specific surface area of the MoS2@Sb2S3@rGO nanomaterial is 182~184 m². 2 / g; and / or, The rod-shaped structure has a rod length of 1.5~2.0 μm; and / or, The cross-sectional radius of the rod-shaped structure is 100~150 nm; and / or, The length-to-length ratio of the rod-shaped structure is (12~16):
1.
16. The negative electrode composite material according to claim 13, characterized in that, The nanosheets have a diameter of 0.1~0.5μm; and / or, The thickness of the nanosheet is 10~30 nm; and / or, The nanosheets have a spacing of 4.4–8.8 Å; and / or, Based on the total mass of the MoS2@Sb2S3@rGO nanomaterials, the content of the rGO material is 5~15wt%; and / or, The thickness of the coating layer is 5~35nm.
17. The negative electrode composite material according to claim 16, characterized in that, The nanosheets have a diameter of 0.2~0.4 μm; and / or, The thickness of the nanosheet is 20-30 nm; and / or, Based on the total mass of the MoS2@Sb2S3@rGO nanomaterials, the content of the rGO material is 8~12wt%; and / or, The thickness of the coating layer is 15~30nm.
18. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative electrode active material, wherein the negative electrode active material includes a negative electrode composite material prepared by the method according to any one of claims 1 to 11 or a negative electrode composite material according to any one of claims 12 to 17.
19. A battery, characterized in that, The battery includes a negative electrode sheet, which is the negative electrode sheet as described in claim 18.
Citation Information
Patent Citations
Preparation method of SnS2 / Sb2S3 / graphene heterostructure lithium ion battery negative electrode material
CN118136788A
Sodium-ion battery material with lamellar cross-linked structure and preparation method of sodium-ion battery material
CN119627081A